Clinical assessment of external fixation in pelvic ring fractures - Hnoosh, Adnan H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Unstable pelvic ring fractures (PRF) are high energy trauma, commonly associated with systemic and soft tissues elements injures, the external fixation as an emergency and final treatment is one of the options in its management.Objective: to evaluate the value and role of external fixation for unstable (PRF) and its clinical outcomes.Patients and methods: twenty one patients with unstable P.R.F have been treated by external fixation , they were 16 men and 5 women ,their  average age was 28 years (range ;18-60 years) , two thirds of the cases were due to road traffic accident , 85% were hemodynamicaly unstable , urological and neurological, anorectal injuries were the commonest associated injuries ,follow up period was 1.6 year range ( 1.00-6 years). Tile classification and Majeed outcome scale had been used.Results: Excellent or good results obtained in 83% of Tile type B injuries , and 44% in type( C) P.R.F. Complications were noted in 42% in the form of skin problems , pin loosening, nerve injurey.Conclusion; External fixation may be useful or even life saving in the acute resuscitation phase of the management of unstable pelvic fracture.